2021
DOI: 10.3390/su13158447
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Socio-Economic Factors Impacting Foreign Trade Development in Port Areas

Abstract: Seaports are an important component of the Russian transport infrastructure. They play a major role in the sustainable development of adjacent territories and the country. Investments in port infrastructure facilitate the introduction of new technologies that accelerate cargo handling, contribute to the efficient use of resources and foreign trade increase. Ports have a major impact on the dynamics of economic indicators in the coastal region, its socio-economic development and environmental condition. In turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Also, it was found that the GDP per person and the use of the Internet helped imports, while digital infrastructure and skills helped exports in a small but positive way. Fedorenko, Yakhneeva, Zaychikova, and Lipinsky (2021) studied the social and economic factors that affected the export and import indicators of Russian ports from 2010 to 2019. Using correlation, regression, panel data analysis, and nonlinear models, it was found that the areas belonging to the Black Sea Corridor (BSC) are all dependent on each other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, it was found that the GDP per person and the use of the Internet helped imports, while digital infrastructure and skills helped exports in a small but positive way. Fedorenko, Yakhneeva, Zaychikova, and Lipinsky (2021) studied the social and economic factors that affected the export and import indicators of Russian ports from 2010 to 2019. Using correlation, regression, panel data analysis, and nonlinear models, it was found that the areas belonging to the Black Sea Corridor (BSC) are all dependent on each other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Distance has a negative impact on trade". Similarily Fedorenko, Yakhneeva, Zaychikova, & Lipinsky [2] analyzed "the impact of socio-economic factors on export and import indicators in five Russian port areas and ten regions from 2010 to 2019. Using the methods of correlation and regression analysis, panel data analysis (fixed-effect models) and nonlinear models, the research revealed dependency patterns for the regions of the Arctic, Baltic, Far Eastern, Azov-Black Sea and Caspian basins.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All of these processes should preferably take place in a stable institutional and legal environment, which is a critical factor for building a supporting business environment and ensuring social equality [25]. Socioeconomic development is also stimulated by an open trade system, which guarantees market availability and the exchange of technology [26]. Population demographics influence the labour market and social resources, affecting socioeconomic development [27].…”
Section: Factors Contributing To Growth In Socioeconomic Developmentmentioning
confidence: 99%